The Design of Optimal Conservation Programs by Electric Utilities Considering Strategic Consumer Behavior - Wirl, Franz (Management Science, 1996)
The practice of utility demand side conservation programs, one of the most topical issues of utility management, provokes strategic reactions of consumers. As a solution of this moral hazard, optimal conservation programs are characterized when the consumers differ either with respect to their subjective time preference or with respect to the level of demand. In particular, we derive incentive compatible conservation schemes that mitigate strategic behavior. These incentives differ starkly from actual programs. First, the costs of conservation may exceed the avoided costs, yet accepting such high costs (at the margin) need not imply a large conservation. Second, such incentive scheme should bypass the inefficient consumers (e.g., the “poor”) but should instead target consumers who act efficiently and have a high demand (e.g., the “rich”).